El corredor urbano Nuevo México-Tesistán en Zapopan, Jalisco: un nuevo rompecabezas inmobilidario - Guerrero, Josefina Lara (2016)
This article examines urban corridors as estructural elements that allows to understand the logic of urban form. Focus on the the road infrastructure and urban corridors, allows us discover the richness represented by these elements, such development inductors linked to mobility, the connection between nodes and the operation in network of the territories. This work is structured in two parts: a theoretical part where the organizer potential of road infrastructure is recognized, and its impact as accelerator in urban sprawl in the Guadalajara Metropolitan Area; an empirical part where takes place an overview of the Nuevo México- Tesisitán urban corridor in the municipality of Zapopan, Jalisco, classified in two models of interpretation: a) as the base of the morphological structure in the northern periphery ; and b) as an enhancer of urban development, leaded by real estate brokers. This will reveal the processes of growth and transformation experienced by the metropolitan area during the last decades.